2014
DOI: 10.1007/978-3-662-44465-8_24
|View full text |Cite
|
Sign up to set email alerts
|

Streaming Kernelization

Abstract: Kernelization is a formalization of preprocessing for combinatorially hard problems. We modify the standard definition for kernelization, which allows any polynomial-time algorithm for the preprocessing, by requiring instead that the preprocessing runs in a streaming setting and uses O(poly(k) log |x|) bits of memory on instances (x, k). We obtain several results in this new setting, depending on the number of passes over the input that such a streaming kernelization is allowed to make. Edge Dominating Set tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…A simple observation shows that any lower bound for parameterized streaming kernels also transfers for the parameterized streaming algorithms. Thus the results of Fafiane and Kratsch [19] also give lower bounds for the parameterized streaming algorithms for these problems. However, our lower bounds have the following advantage over the results of [19]:…”
Section: C1 Matching and Hitting Set Lower Boundsmentioning
confidence: 80%
See 2 more Smart Citations
“…A simple observation shows that any lower bound for parameterized streaming kernels also transfers for the parameterized streaming algorithms. Thus the results of Fafiane and Kratsch [19] also give lower bounds for the parameterized streaming algorithms for these problems. However, our lower bounds have the following advantage over the results of [19]:…”
Section: C1 Matching and Hitting Set Lower Boundsmentioning
confidence: 80%
“…Fafianie and Kratsch [19] gave lower bounds for several parameterized problems. In particular, they showed that: • Any t-pass kernel for CLUSTER EDITING(k) and MINIMUM FILL-IN(k) requires Ω(n/t) space.…”
Section: C1 Matching and Hitting Set Lower Boundsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, very few results are known in this direction. Chitnis et al [CCHM15] and Fafianie and Kratsch [FK14] introduced parameterized graph stream algorithms which may only use o(n) space with some promise of the size of the solution. This parameterized setting has been further investigated in [CCE + 16].…”
Section: Introductionmentioning
confidence: 99%
“…Another measure of the performance of a kernelization is the number of passes over the input the kernelization makes [11].…”
mentioning
confidence: 99%